Building Trust in the Use of Sharia Fintech Services: A Literature Review - Oktafian Histori S. (Institut Agama Islam Negeri (IAIN) Curup, 2022)
Purpose: This study analyzes how to build trust in the use of sharia fintech services in Indonesia by considering the benefits and risks faced by users.Design/Method/Approach: Descriptive qualitative research design with a literature review approach was used in this study. The data collection method was documentation technique while the data analysis technique used conclusion drawing technique to obtain information about a message objectively and systematically.Findings: The results of the study show that building trust in the use of sharia fintech services is something that must be done by sharia fintech startup companies since Indonesia is a country with a majority Muslim community. Trust is built by maximizing the benefits obtained and minimizing the risks that will be faced by users.Originality/Values:This research contributes to provide valuable information regarding how to build trust in the use of sharia fintech services in Indonesia in the context of developing the sharia industry and economy.